2014
DOI: 10.1186/1471-2164-15-518
|View full text |Cite
|
Sign up to set email alerts
|

A 24-48 h fed Amblyomma americanum tick saliva immuno-proteome

Abstract: BackgroundMultiple tick saliva proteins, the majority of which are unknown, confer tick resistance in repeatedly infested animals. The objective of this study was to identify the 24-48 h fed Amblyomma americanum tick saliva immuno-proteome. The 24-48 h tick-feeding phase is critical to tick parasitism as it precedes important events in tick biology, blood meal feeding and disease agent transmission. Fed male, 24 and 96 h fed female phage display cDNA expression libraries were biopanned using rabbit antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
100
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 237 publications
15
100
0
Order By: Relevance
“…Nevertheless it became clear that the sheer quantity of proteins and other products of the salivary glands (Alarcon‐Chaidez, 2014) make assignment to particular functions such as cement formation difficult. To address this problem, temporary expression patterns of the salivary glands were analysed (Radulovic et al ., 2014; Kim et al ., 2016; Bullard, Williams & Karim, 2016), showing which salivary products were produced at certain points during feeding. These subsets of proteins were then tested for their functions by specific inactivation in living ticks and verification in feeding trials (Kim, Curran & Mulenga, 2014).…”
Section: Historical Perspective On Cement Researchmentioning
confidence: 99%
“…Nevertheless it became clear that the sheer quantity of proteins and other products of the salivary glands (Alarcon‐Chaidez, 2014) make assignment to particular functions such as cement formation difficult. To address this problem, temporary expression patterns of the salivary glands were analysed (Radulovic et al ., 2014; Kim et al ., 2016; Bullard, Williams & Karim, 2016), showing which salivary products were produced at certain points during feeding. These subsets of proteins were then tested for their functions by specific inactivation in living ticks and verification in feeding trials (Kim, Curran & Mulenga, 2014).…”
Section: Historical Perspective On Cement Researchmentioning
confidence: 99%
“…We also identified a number of proteins with homology to putative tick proteins that are suspected to be involved in host-parasite molecular interactions (Radulovic et al 2014). Among these were homologs of calmodulin, calreticulin, lipocalin, and glutathione-S-transferase (Supp.…”
Section: Other Proteins Of Interestmentioning
confidence: 99%
“…In an interesting approach to identify secreted tick salivary proteins (TSPs) Radulovic et. al., [40] and Lewis et. al., [41] used antibodies to 24-48 h tick saliva proteins [42,43] to immunoscreen phage display cDNA expression libraries to identify 24-48 h Amblyomma americanum and 24 h I. scapularis immunogenic tick saliva proteins.…”
Section: Introductionmentioning
confidence: 91%
“…moubata tHBP, referred to as moubatin, demonstrated inhibition of collagen induced platelet aggregation [96]. In a recent study, lipocalins/HBPs/FABPs were identified among 24-48 h A. americanum immunogenic tick saliva proteins [40] suggesting that these proteins are part of the tick saliva proteins that confer anti-tick resistance in repeatedly infested animals. It is notable that in Radulovic et al, [40], alongside lipocalins/HBPs, a leukotriene B4-like protease was also found among 24-48 h A. americanum immunogenic tick saliva proteins.…”
Section: Lipocalins/tick Histamine-binding Proteins (Thbp)/fatty Acidmentioning
confidence: 99%
See 1 more Smart Citation